Paracrine activation of hepatic stellate cells in platelet‐derived growth factor C transgenic mice: Evidence for stromal induction of hepatocellular carcinoma. Issue 4 (16th September 2013) - Wright, Jocelyn H.; Johnson, Melissa M.; Shimizu‐Albergine, Masami; Bauer, Renay L.; Hayes, Brian J.; Surapisitchat, James; Hudkins, Kelly L.; Riehle, Kimberly J.; Johnson, Simon C.; Yeh, Matthew M.; Bammler, Theodor K.; Beyer, Richard P.; et al.
<x xml:space="preserve">Abstract</x> Cirrhosis is the primary risk factor for the development of hepatocellular carcinoma (HCC), yet the mechanisms by which cirrhosis predisposes to carcinogenesis are poorly understood. Using a mouse model that recapitulates many aspects of the pathophysiology of human liver disease, we explored the mechanisms by which changes in the liver microenvironment induce dysplasia and HCC. Hepatic expression of platelet‐derived growth factor C (PDGF‐C) induces progressive fibrosis, chronic inflammation, neoangiogenesis and sinusoidal congestion, as well as global changes in gene expression. Using reporter mice, immunofluorescence, immunohistochemistry and liver cell isolation, we demonstrate that receptors for PDGF‐CC are localized on hepatic stellate cells (HSCs), which proliferate, and transform into myofibroblast‐like cells that deposit extracellular matrix and lead to production of growth factors and cytokines. We demonstrate induction of cytokine genes at 2 months, and stromal cell‐derived hepatocyte growth factors that coincide with the onset of dysplasia at 4 months. Our results support a paracrine signaling model wherein hepatocyte‐derived PDGF‐C stimulates widespread HSC activation throughout the liver leading to chronic inflammation, liver injury and architectural changes. These complex changes to the liver microenvironment precede the development of HCC. Further, increased PDGF‐CC levels were observed in livers of patients with nonalcoholic fatty steatohepatitis and correlate with the stage of disease, suggesting a role for this growth factor in chronic liver disease in humans. PDGF‐C transgenic mice provide a unique model for the in vivo study of tumor–stromal interactions in the liver.